Hypotensive and antihypertensive effects of Pterocarpus santalinoides stem barks aqueous extract on oxidized palm oil and sucrose-induced hypertensive rats - Chinte Yamjom Ramatou,; Gounoue Kamkumo Raceline,; Metchi Donfack mirielle,; Bilanda Danielle Claude,; Dimo Théophile, (International Journal of Phytomedicine, 2019)
Objective: This study was aimed to evaluate the hypotensive and antihypertensive effects of the stem barks aqueous extract of Pterocarpus santalinoides (AEPS) on oxidized palm oil and sucrose-induced hypertensive rats. Methods: Hypotensive effects of AEPS, were evaluated in Wistar rats by intravenous injection of the extract (5, 10, 20 and 30 mg/kg). The arterial pressure and heart rate were directly recorded. The action mechanism through which the extract exhibits hypotensive effect was performed. Antihypertensive effects of AEPS were evaluated by administrating the enriched diet in oxidized palm oil and sucrose (DOS) concomitantly with AEPS (50, 100 and 200 mg/kg) during 8 weeks. Results: AEPS provoked a significant immediate decrease of mean blood pressure and heart rate. Atropine and reserpine, reduced significantly (p < 0.01) the hypotensive effect of P. santalinoides. The enriched diet in oxidized palm oil and sucrose significantly increased the blood pressure and heart rate (p < 0.001) by the increase (p < 0.001) of total cholesterol, triglycerides, LDL-cholesterol and a decrease of HDL-cholesterol. DOS also increased the liver (AST and ALT) and kidney (urea, creatinine) marker levels. The activity of SOD, catalase and MDA levels were significantly increased. The AEPS prevented the increase (p < 0.001) in blood pressure and heart rate. The Lipid profile, liver and kidney functions and oxidative stress markers were also improved. Conclusion: Pterocarpus santalinoides exhibits a hypotensive activity through muscarinic cholinergic receptors and sympatic central nervous system. It also prevents DOS-induced hypertension by attenuating hyperlipidemia, oxidative stress, liver and kidney damages initiated by DOS.